PENGARUH PENAMBAHAN VITAMIN BATERAI VITTA-Q TERHADAP LOAD TEST PADA LEAD ACID BATTERY TIPE LIQUID VENTED 12V 5AH - Amirudin, Erwan (Jurnal Nosel, 2014)
The purposes of this research: (1) To investigate the effect of using vitta-Q battery to load teston lead acid battery12V 5Ah liquid vented type. (2) To investigate the voltage of load test lead acid battery12V 5Ah liquid vented type after using vitta-q battery vitamin. Based on the research result, it can be concluded: (1) The measurement result after using vitta-Q battery vitamin on lead acid battery 12V 5Ah liquid vented type by using digital load tester provides the highest load test of 2 ml vitta-Q battery vitamin per cell is 8.2 V and it stays indicator parameter of 6.5V?9.6 V, that showing the battery is in good condition and needs for a recharge. (2) The measurement result after using of vitta-Q battery vitamin on lead acid battery12V 5Ahliquid vented type by using digital load tester provides the lowestload test of 3.5 ml vitta-Q battery vitamin per cell is 6.3 V showing the battery is on damaged condition and needs for a replacement. (3) The measurement result after using of vitta-Q battery vitamin on lead acid battery 12V 5Ah liquid vented type by using digital load tester of 2.5 ml battery vitamin per cell, as suggested by the company standard, provides the load tester is in 7.7 V and stays in the indicator parameter of 6.5 V ? 9.6 V, Showing the battery is on good condition and needs for a recharge.